2017
DOI: 10.1002/jbt.21892
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the growth and plasma membrane H+‐ATPase inhibitory activity of ebselen and structurally related selenium‐ and sulfur‐containing compounds in Candida albicans

Abstract: Ebselen (EB, compound 1) is an investigational organoselenium compound that reduces fungal growth, in part, through inhibition of the fungal plasma membrane H -ATPase (Pma1p). In the present study, the growth inhibitory activity of EB and of five structural analogs was assessed in a fluconazole (FLU)-resistant strain of Candida albicans (S2). While none of the compounds were more effective than EB at inhibiting fungal growth (IC ∼ 18 μM), two compounds, compounds 5 and 6, were similar in potency. Medium acidif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
3
20
0
3
Order By: Relevance
“…The IC 50 of ebselen for C. albicans was found to be 11 μM, in agreement with the previously reported value of 14 μM (18). …”
Section: Resultssupporting
confidence: 92%
“…The IC 50 of ebselen for C. albicans was found to be 11 μM, in agreement with the previously reported value of 14 μM (18). …”
Section: Resultssupporting
confidence: 92%
“…The tremendous efforts in this area has led to the identification of many bioactive structures [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Several enzymes, among them thioredoxin reductase [ 36 , 48 ], bacterial urease [ 49 ], and plasma membrane H+-ATPase [ 50 , 51 , 52 ], were suggested as targets for organoselenium compounds with antimicrobial properties. Furthermore, it has been reported that the antiviral effects of organoselenium compounds might be related to the inhibition of hepatitis C virus NS3 helicase [ 28 ], HIV-1 capsid dimerization [ 29 ], and nucleocapsid protein 7 [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura a vários relatos de albuminas vegetais com atividade antifúngica (Cândido et al, 2011;Ribeiro et al, 2012). (Kongstad et al, 2015;Orie et al, 2017). Devido a sua grande relevância, a H + -ATPase surge como um alvo para a ação de novos agentes antifúngicos (Kongstad et al, 2015;Orie et al, 2017).…”
Section: Resultsunclassified